EDUKASI PENINGKATAN PEMAHAMAN AIR BERSIH DI DESA SINDANGMULYA - Sumino, Sumino; Ilyas Sikki, Muhammad; Supratno, Setyo (Universitas Islam 45 Bekasi, 2024)
The need for clean water is currently very urgent to meet industrial and household needs. Clean water has an important role for health for the wider community, including pregnant mothers. The understanding related to clean water among residents in Sindangmulya village before and after receiving education and training, their understanding of clean water is increasing based on the data list of questions asked by participants with interactive dialogue from questions and answers discussed in two directions proved that there was a significant increase in understanding of clean water both for daily living needs and for drinking water consumption so that they could maintain a healthy lifestyle for their families. Education and understanding regarding clean water is a very relevant program to support the healthy lifestyle of Sindangmulya village residents. Increased understanding of clean water for Sindangmulya village residents is reflected in simple techniques based on clean water quality standards according to regulations that apply in everyday life where residents are very critical of checking clean water before use. This increase in understanding of clean water also indirectly helps reduce unnecessary expenses such as purchasing refillable drinking water and family medication.